Global hierarchical collapse in molecular clouds. Towards a comprehensive scenario. Issue 3 (3rd October 2019) - Vázquez-Semadeni, Enrique; Palau, Aina; Ballesteros-Paredes, Javier; Gómez, Gilberto C; Zamora-Avilés, Manuel
Abstract: We present a unified description of the scenario of global hierarchical collapse (GHC). GHC constitutes a flow regime of (non-homologous) collapses within collapses, in which all scales accrete from their parent structures, and small, dense regions begin to contract at later times, but on shorter time-scales than large, diffuse ones. The different time-scales allow for most of the clouds' mass to be dispersed by the feedback from the first massive stars, maintaining the cloud-scale star formation rate low. Molecular clouds (MCs), clumps, and cores are not in equilibrium, but rather are either undergoing contraction or dispersal. The main features of GHC are as follows: (1) The gravitational contraction is initially very slow, and begins when the cloud still consists of mostly atomic gas. (2) Star-forming MCs are in an essentially pressureless regime, causing filamentary accretion flows from the cloud to the core scale to arise spontaneously. (3) Accreting objects have longer lifetimes than their own free-fall time, due to the continuous replenishment of material. (4) The clouds' total mass and its molecular and dense mass fractions increase over time. (5) The clouds' masses stop growing when feedback becomes important. (6) The first stars appear several megayears after global contraction began, and are of low mass; massive stars appear a few megayears later, in massive hubs. (7) The minimum fragment mass may well extend into the brown-dwarf regime. (8) Bondi–Hoyle–Lyttleton-like accretion occurs at both the protostellar and the core scales, accounting for an IMF with slope d N /d M  ∝  M −2 . (9) The extreme anisotropy of the filamentary network explains the difficulty in detecting large-scale infall signatures. (10) The balance between inertial and gravitationally driven motions in clumps evolves during the contraction, explaining the approach to apparent virial equilibrium, from supervirial states in low-column density clumps and from subvirial states in dense cores. (11) Prestellar cores adopt Bonnor–Ebert-like profiles, but are contracting ever since when they may appear to be unbound. (12) Stellar clusters develop radial age and mass segregation gradients. We also discuss the incompatibility between supersonic turbulence and the observed scalings in the molecular hierarchy. Since gravitationally formed filaments do not develop shocks at their axes, we suggest that a diagnostic for the GHC scenario should be the absence of strong shocks in them. Finally, we critically discuss some recent objections to the GHC mechanism.